Alternative ways of accelerating compulsory primary education in Thailand - Praiwan, Grarng 1931-
This study formulates educational strategies for Thailand to identify and utilize potential resources of the community to accelerate and attain full compulsory seven-year schooling. Subjects consisted of 874 head teachers, 747 abbots and 852 parents of fourth grade pupils from 27 districts. They are generally receptive to eight proposed alternatives, namely: cooperation between the wat and the school, building of schools by both abbots and head teachers, the use of salawats as classrooms, recruitment of monks as teachers, utilization of monks' help in teaching, introduction of double shifts, extension of the school year and increase in the salary of teachers for additional sixty days of teaching.